Charge transfer resistance reduction by the interlayer distance expansion of Ni-Al layered double hydroxide for nickel-metal hydride battery anode. (20th April 2018) - Maki, Hideshi; Inoue, Masayoshi; Mizuhata, Minoru
Abstract: The Ni-Al layered double hydroxide (Ni-Al LDH) as an anode in nickel-metal hydride batteries is synthesized by liquid phase deposition (LPD) and the interlayer distance of the Ni-Al LDH is enlarged by the anionic exchanges from F − form to halide anion forms, oxo anion forms, complex anion forms, and surface-active agent anion forms, namely, ca. from 320 p.m. to a maximum of 2500 p.m. Then, we fabricate electrodes from the anion-exchanged LDH and study the relations between interlayer distance and internal resistance. The interlayer distances of the Ni-Al LDH, which are calculated from d 003, increase with the diameter of the intercalated anions. The interlayer distance of the LDH depends on the molecular shape and size of the intercalated anions. The charge transfer resistance( R ct ) decreases by half when the LDH interlayer distance increases to about 400 p.m., and the activation energy for charge transfer(Δ E a ) also decreases with increasing LDH interlayer distance. Furthermore, the electron transfer and the ion transport between the collector (i.e., Ni foam) and the active material especially contribute to the decrease of R ct and Δ E a of the electrode compared with those between the conductive assistant (i.e., carbon black powder). Graphical abstract: Highlights: Ni-Al LDH was synthesized by the liquid phase deposition. Interlayer distance of the Ni-Al LDH was enlarged by the anionic exchanges. Interlayer distance depended on the shape and size of the intercalated anions. R ct decreased by half when the interlayer distance increased to 400 p.m. Ni-Al LDH on current collector especially contribute to the decrease of R ct .